Student perceptions of learning environment: disciplinary program versus general education classrooms. Issue 4 (2nd October 2018) - Lerdpornkulrat, Thanita; Koul, Ravinder; Poondej, Chanut
Abstract: The purpose of this study was to examine student perceptions of the learning environment in their program major and general education classrooms. The participants were 870 undergraduate students majoring in engineering, fine arts, education, economics and nursing programs at a university in Thailand. We found significant differences in the perceptions of the classroom learning environment across various disciplines. Engineering and economics students perceived the learning environment in general education classrooms as more cooperative than the learning environment in program major classrooms. Fine arts and nursing students perceived greater involvement among students in the program major classrooms than in the general education classrooms. Our findings contribute to the body of research on inter-disciplinary differences in classroom learning environments in universities and the ways in which these differences may impact student learning outcomes.